2019
DOI: 10.13044/j.sdewes.d6.0245
|View full text |Cite
|
Sign up to set email alerts
|

Method for Optimization of the Gasifier Recovery Zone Height

Abstract: The article provides the results of experimental studies of the effect of air introduction into a gasifier, the fuel particle size, and the recovery zone height on a content of carbon monoxide in wood gas. The mathematical models of wood gas formation presented in the scientific research have uncertain boundary conditions. For adequate use of the mathematical models numerous hypotheses are needed. Therefore, it is essential to acquire experimental data in the actual range of gasifier operation parameters. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The study conducted by National Academies of Sciences, Engineering, and Medicine (the United States of America) has revealed that motives and thinking are two important psychological factors influencing students' success in the context of studying at the tertiary educational institution. The results of the students' survey from one of the colleges in the United States have shown that important psychosocial factors influencing students' success in the learning process are as follows: academic self-efficacy, organization and attention to studying, stress and time management, features of students' involvement in college, emotional satisfaction (Golub et al, 2020a;Golub et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted by National Academies of Sciences, Engineering, and Medicine (the United States of America) has revealed that motives and thinking are two important psychological factors influencing students' success in the context of studying at the tertiary educational institution. The results of the students' survey from one of the colleges in the United States have shown that important psychosocial factors influencing students' success in the learning process are as follows: academic self-efficacy, organization and attention to studying, stress and time management, features of students' involvement in college, emotional satisfaction (Golub et al, 2020a;Golub et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…where V -volume of 0.1 N Trilon B solution used for titration; C -concentration of Trilon B solution; W -aliquot part of the sample. The electrometric method for determining salinity is based on measuring the relative electrical conductivity of water using a special device -a conductometer, which makes it possible to accelerate and increase the accuracy of its determination in comparison with other methods [28]. The operating principle of conductometer is based on the direct dependence of the electrical conductivity of water (current strength in a constant electric field created by the electrodes of the device) on the number of compounds dissolved in water.…”
Section: Issn 2224-5286mentioning
confidence: 99%
“…Therefore, considering algorithmic thinking as a new dimension of learning in higher education is feasible and very vital for Ukrainian universities. First of all, for a better understanding of algorithmic thinking, it is necessary to determine its essence, main properties, and characteristics (Kostruba, 2018;Golub et al, 2020).…”
Section: The Essence Main Properties and Characteristics Of Algorithmic Thinkingmentioning
confidence: 99%